Saliva acid phosphatases: genetic studies - Tan, Soon Guan; Ashton, G. C. (Karger, 1976)
Acid phosphatases from human saliva have been demonstrated by the zymogram technique. Six phenotypes were found. Family and population studies suggested that the phenotypes are the product of two loci, Sap-A with three alleles A, A' and O, and Sap-B with two alleles B and O.